Phenological trait evaluation and correlation studies for yield and its components in parents and F2 progeny lines of Indian mustard (Brassica juncea L.) - Monika; Ram C Yadav; Neelam R Yadav; Ram Avtar; Dhiraj Singh (Journal of Oilseed Brassica, 2026)
Brassica juncea commonly known as Indian mustard is economically very important crop because of its high oil contentand superior oil quality. It is utilized worldwide as an oilseed, a condiment, vegetable, green manure, forage and fodderand cultivated primarily in tropical and sub-tropical countries. Study of Indian mustard parental genotypes of diverseorigin RB50 and Kranti and their 157 F2 progeny lines for various yield related different characters revealed considerablevariability for all the characters under study. Yield and yield related attributes like number of primary branches/plant,number of secondary branches/plant, number of silique/plant, main raceme length, number of siliqua on main raceme,siliqua length, number of seeds/siliqua, 1000 seeds weight and seed yield were recorded for estimation of yield attributesin F2 generation. Physiological traits of relative water content and electrolyte leakage were taken to study the effect ofvarious yield affecting physiological traits on potential yield in parent and progeny lines for better selection of goodyielding genotypes. 21 lines were selected as promising lines on the basis of their good yield (more than both theparental genotypes) and better physiology as they have more relative water content and less electrolyte leakage.Therefore, they survive stress conditions more effectively and can serve as good genetic material for further progenyanalysis and generation of higher yielding genotypes in future generations.